MASSTIGE PRODUCTS AND QUALITY OF LIFE - Aurora Rahyu Fasya; Burhanudin Burhanudin (Jurnal Ekonomi, 2022)
The culinary world today is not only food that is in demand, drinks are also quite popular. Masstige stands for prestige for the masses and of Starbucks products fall into this category. This study aims to determine the effect of perceived service performance and minimalism on quality of life and in turn, purchase behavior. There were 302 customers of Starbucks participated in the study. The data was analyzed using SEM (Structural Equition Modeling). The results showed perceived service performance and minimalism had significant effects on quality of life and in turn, purchase behavior.